The Burden of the Nondiversifiable Risk of Entrepreneurship - Hall, Robert E; Woodward, Susan E (American Economic Review, 2010)
Entrepreneurship is risky. We study the risk facing a well-documented and important class of entrepreneurs, those backed by venture capital. Using a dynamic program, we calculate the certainty-equivalent of the difference between the cash rewards that entrepreneurs actually received over the past 20 years and the cash that entrepreneurs would have received from a risk-free salaried job. The payoff to a venture-backed entrepreneur comprises a below-market salary and a share of the equity value of the company when it goes public or is acquired. We find that the typical venture-backed entrepreneur received an average of $5.8 million in exit cash. Almost three-quarters of entrepreneurs receive nothing at exit and a few receive over a billion dollars. Because of the extreme dispersion of payoffs, an entrepreneur with a coefficient of relative risk aversion of two places a certainty equivalent value only slightly greater than zero on the distribution of outcomes she faces at the time of her company's launch. (JEL G24, G32, L26, M13)